SOSIALISASI PEMANFAATAN LIMBAH KULIT DURIAN SEBAGAI PRODUK BRIKET DI WILAYAH WARGA RT. 19 KELURAHAN 1 ILIR KECAMATAN ILIR TIMUR II PALEMBANG SUMATERA SELATAN - Lety Trisnaliani; Ahmad Zikri; Erlinawati Akil (Politeknik Negeri Sriwijaya, 2018)
Durian waste is the basic ingredient of making this briquette and just piling up into waste in the neighborhood where it sells and can not provide economic value. Now the material we used to call environmental waste will turn into alternative fuels. Through the process of processing, durian waste will be fuel in the form of briquettes and this product will have a fairly high selling value. The briquettes also smell good when used, making them suitable for the food industry, both large and large scale. Because of these several advantages, durian leather briquettes have wide open market potential in both local, domestic and export markets. The method implemented is to socialize the utilization of durian skin by spreading knowledge with the manufacture and processing of durian skin so as to produce the outcome of durian briquette product as a substitute of fuel in the era of expensive energy.